The tug-of-war between sports and physical activity anxiety in quest for self-actualization among university students - Tagare, Jr., Ruben L.; Martinez, Norge D.; C. Nadela, Lara Ivanah; Janito, Cheeze R.; Esto, Jomar B.; Elumbaring, Jerum B.; Francisco, Jemwell B.; P. Esponja, Joanna Caryl; Java, Vinus P.; Adlaon, Gauvin; B. Labarda, Sarah Jane; Lobo, Joseph; Longakit, Jet C.; Panganiban, Teejay D. (Institute of Advanced Engineering and Science, 2025)
This study investigates the relationship between sports and physical activity anxiety and self-actualization among university students. Utilizing a quantitative research design with a descriptive correlation approach, the study involved 2,043 respondents selected through simple random sampling. Two primary instruments were employed: the physical activity and sport anxiety scale (PASAS) to measure anxiety levels and the index of self-actualization to assess self-actualization traits. Data were analyzed using descriptive statistics and Spearman’s rho correlation coefficient to explore the relationships between the variables. Results revealed that respondents exhibited low levels of sports and physical activity anxiety and moderate levels of self-actualization. Notably, a significant negative correlation was identified between sports and physical activity anxiety and self-actualization. These findings imply that higher anxiety related to sports and physical activities is associated with lower levels of self-actualization, highlighting the need for supportive environments that mitigate anxiety in physical activity contexts. The study underscores the importance of implementing strategies to reduce anxiety and promote self-discovery, ultimately fostering resilience and personal growth among students.